THE EFFECT OF COMPANY SIZE, COMPANY AGE, PROFITABILITY, AND AUDIT DELAY ON ACCURACY TIME OF SUBMISSION OF COMPANY FINANCIAL REPORTS REGISTERED CONSUMER CYCLICALS SECTOR ON THE INDONESIA STOCK EXCHANGE IN 2024 - Dinda Aura Malika; Nurmala; Anita Kusuma Dewi (RADJA PUBLIKA, 2026)
The timeliness of financial statement submission is an essential aspect of corporate transparency and accountability, particularly for publicly listed companies. Delayed financial reporting may reduce the relevance of accounting information and negatively affect investors' decision-making. This study aims to examine the effects of firm size, firm age, profitability, and audit delay on the timeliness of financial statement submission among Consumer Cyclicals companies listed on the Indonesia Stock Exchange (IDX) in 2024. This research employed a quantitative approach using secondary data obtained from the annual reports of Consumer Cyclicals companies listed on the IDX. The sample consisted of 141 companies selected through purposive sampling. The data were analyzed using descriptive statistics and binary logistic regression. The results indicate that firm size, firm age, and profitability have no significant effect on the timeliness of financial statement submission. In contrast, audit delay has a significant negative effect on the timeliness of financial reporting, indicating that a longer audit completion period reduces the likelihood of companies submitting their financial statements on time. The logistic regression model demonstrates good model fit and explains 84.6% of the variation in the timeliness of financial statement submission. These findings suggest that improving the efficiency of the audit process is a key factor in enhancing timely financial reporting among Consumer Cyclical companies. Therefore, companies are encouraged to strengthen coordination with auditors and improve the effectiveness of their financial reporting processes to ensure compliance with regulatory reporting deadlines.